1970
DOI: 10.1002/recl.19700890114
|View full text |Cite
|
Sign up to set email alerts
|

A general method for the preparation of cumulenic ethers and thioethers

Abstract: Solutions of lithiated cumulenic ethers and bis-ethers R2CH=C=C=C(Li)OR3 and R10CH=C=C=C(Li)OR3 can be obtained by treatment of the compounds R10CH(R2)C=CCHz0R3 and R10CH2C=CCH(OR3)z respectively with 2 equivalents of butyllithium in ether. Reaction of these solutions with HzO, DzO, methyl iodide, a-chloroethers or ketones gives the cumulenic compounds or their derivatives in good yields.Solutions of lithiated cumulenic thioethers R2CH=C=C=C(Li)SR3 are obtained in an analogous way, but hydrolysis affords the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Brandsma et al reported a quite general procedure for the preparation of butatrienyl ethers and thioethers by basic treatment of bispropargylic diethers or dithioethers containing a primary propargylic functional methylene groups (CH 2 X, X = O, S), followed by a trapping of the butatrienyllithium intermediates with electrophiles (Scheme ) . Butatrienyl ethers were thus obtained in quite good yields, while butatrienyl thioethers were generally obtained in mixture with their enynyl thioether isomers, probably arising from the hydrolysis of the enynyl form of the lithiated intermediates.…”
Section: Synthesis Of Butatrienes By Transformation Of Preformed C4 P...mentioning
confidence: 99%
“…Brandsma et al reported a quite general procedure for the preparation of butatrienyl ethers and thioethers by basic treatment of bispropargylic diethers or dithioethers containing a primary propargylic functional methylene groups (CH 2 X, X = O, S), followed by a trapping of the butatrienyllithium intermediates with electrophiles (Scheme ) . Butatrienyl ethers were thus obtained in quite good yields, while butatrienyl thioethers were generally obtained in mixture with their enynyl thioether isomers, probably arising from the hydrolysis of the enynyl form of the lithiated intermediates.…”
Section: Synthesis Of Butatrienes By Transformation Of Preformed C4 P...mentioning
confidence: 99%